Criminological Review of Premeditated Murder Perpetrators (Based on Personality Theory: Case of KH. Mochamad Tarma Hantono, Karawang) - Tiawardana, Triadi; Maman`, Ade; Setiady, Tri (Ipso Jure, 2025)
This paper discusses the criminological review of premeditated murder perpetrators based on personality characteristic theory, focusing on the case of KH. Mochamad Tarma Hantono and associates in Karawang. The study aims to explore the factors that lead individuals to commit premeditated murder in connection with personality theory and to analyze the criminal liability of the perpetrators. The research adopts a normative juridical method, utilizing literature and secondary data to examine relevant regulations and scholarly works. The study finds that factors influencing the commission of premeditated murder can be categorized into internal and external elements. Internal factors include motivation, urgency, economic needs, intelligence, age, and gender. External factors involve education, social environment, employment, and community security vulnerabilities. These aspects are examined through Article 340 of the Criminal Code, which stipulates penalties for premeditated murder, such as the death penalty, life imprisonment, or imprisonment for up to 20 years. The analysis reveals that personality characteristics, including structural and dynamic differences between criminals and non-criminals, play a significant role in understanding premeditated murder. Additionally, criminal psychological theories suggest the importance of behavioral prediction and the distinction among various types of criminals. The research concludes that premeditated murder is influenced by a combination of personality traits and external factors, and perpetrators are legally accountable under the provisions of criminal law.